A broad-spectrum solar energy power system by hybridizing stirling-like thermocapacitive cycles to dye-sensitized solar cells. (March 2023) - Zhao, Qin; Lai, Cong; Zhang, Houcheng; Hu, Ziyang
Abstract: To maximally utilize inlet sunlight, a novel dye-sensitized solar cell-based hybrid system containing a solar selective absorber and a Stirling-like thermocapacitive cycle is theoretically put forward. Energy efficiencies and output powers of dye-sensitized solar cell, Stirling-like thermocapacitive cycle and hybrid system are deduced. Feasibility as well as competitiveness of hybrid system are expounded through comprehensive comparisons. Numerical results show that output power density and energy efficiency of hybrid system are, respectively, 148.96 W m - 2 and 14.90%, which are, respectively, 93.58% and 204.70% superior to that of standalone dye-sensitized solar cell. Moreover, ponderable parametric studies are performed to examine how key variables affect the hybrid system performance. It is found that greater operating temperature of dye-sensitized solar cell, charging endpoint voltage of Stirling-like thermocapacitive cycle or thermal conductance coefficients between Stirling-like thermocapacitive cycle and dye-sensitized solar cell/solar selective absorber subsystems as well as environment are favorable to the hybrid system performance, while higher environment temperature and discharging endpoint voltage of Stirling-like thermocapacitive cycle are unfavorable variables. In addition, the thickness and porosity of nano porous TiO2 semiconductive film can be structurally optimized to improve the hybrid system performance.